The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5336/dentalsci.2014-42862
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Dental Injuries in Malatya: A Retrospective Study

Abstract: Ö ÖZ ZE ET T A Am ma aç ç: : Dental travmatik yaralanmalar, süt ve daimi dişlerde sık gözlenen problemler arasında yer almaktadır. Dünya genelinde dental travmatik yaralanmalar çeşitli frekanslarda rapor edilmesine karşın; Doğu Anadolu'da dental travma sıklığı ile ilgili veriler sınırlıdır. Bu çalışmada, İnönü Üniversitesi Diş Hekimliği Fakültesi Pedodonti Anabilim Dalına dört yıllık süre (Ocak 2010-Ocak 2014) içinde başvurmuş olan 1-13 yaş arası çocuk hastalarda dental travma sıklığı, ilişkili faktörler ve te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…While some studies align with this finding, 5,31,49,50 others report summer 24,28,32,51,52 or autumn 26 as the most common TDI seasons. Falls during playtime or at home are the primary cause, with 38.27% from falling and 27.7% from bicycle or roller skate accidents, which is supported by literature 1,5,7,26,28,30,37,49,51,53–57 . Upper incisors are the most affected teeth in both primary and permanent dentition, due to their prominent position and other predisposing factors 5,25,26,28,31–35,38,58–63 .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…While some studies align with this finding, 5,31,49,50 others report summer 24,28,32,51,52 or autumn 26 as the most common TDI seasons. Falls during playtime or at home are the primary cause, with 38.27% from falling and 27.7% from bicycle or roller skate accidents, which is supported by literature 1,5,7,26,28,30,37,49,51,53–57 . Upper incisors are the most affected teeth in both primary and permanent dentition, due to their prominent position and other predisposing factors 5,25,26,28,31–35,38,58–63 .…”
Section: Discussionmentioning
confidence: 80%
“…They emphasize the need for a proper approach to lateral luxation as well as to all TDIs, since it has lifelong concerns for a patient. Studies differ on injury types in supporting tissues, and some indicate subluxation, extrusion, or intrusion as most common 32,37,40,56 . Flexible bone structure and periodontal ligament explain the incidence of luxation injuries during primary dentition 5,19,51,68,70,71 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, family physicians were shown photos of 2 cases (Figure 1, 2) involving an avulsed tooth and an enamel-dentin fracture which are among the most prevalent TDIs occurring in our region and their responses were reviewed (25). 53.5% of the physicians stated that they have come across a TDI patient at least once in their practice.…”
Section: Discussionmentioning
confidence: 95%
“…tarafından yapılan çalışmaya göre 7-12 yaş aralığındaki çocuklarda DMF(t) değeri 1,39 (±1,98) olarak bulunmuştur. 20 Gökalp ve ark.nın ülkemizde 12 yaşındaki kırsal ve kentsel alanlarda yaşayan ço-cuklarda yaptığı çalışmada DMF(t) değerleri sıra-sıyla 2,0 (±2,2) ve 1,9 (±2,1) olarak hesaplanmıştır.…”
unclassified